Study of health status and morbidity pattern in 5-18 years Birhor children: A primitive tribe of Chhattisgarh - Kurrey, Virendra Kumar; Lokesh, Sharma; Rakesh, Nahrel; Sharja, Phuljhele (Indian Journal of Child Health, 2022)
Background: A 5-18 years children constitute about 31.6% of the Indian population. This age group, particularly children of underprivileged class are at higher risk to suffer from malnutrition and health-related condition and needs to be developed and cultivate for the country to progress. Objectives: To study the health status and morbidity pattern in Birhor children (5-18 years) of Dharamjaigarh Block Raigarh, Chhattisgarh. Materials and Methods: This cross-sectional study was conducted among 50 Birhor children (boys and girls of 5-18 years age). Anthropometric indices were used to determine the health status and variants, i.e., socioeconomic condition, cultural feeding practices, and family literacy were studied which could have an influence on thehealth status. Morbidity pattern was also studied by assessing the current illness by clinical examination and history of past illnesses. Results: The prevalence of underweight was 32.5%, while stunting was found in 22% and thinness in 24% children. Prevalence of common morbidities was as follows: Pallor (66%), conjunctival xerosis (38%), caries teeth (32%), skin infections (24%), and lymphadenopathy (22%). History of acute febrile illness (non-malaria) was present in 46% cases, malaria in 16%, jaundice in 16%,envenomation/intoxication/animal bites in 16%, and history of hospitalization was present in 12% cases, and trauma/accidents was there in 12% cases in the past. Conclusion: In this study, we found a high prevalence of morbidities in Birhor tribal; though, the health status of these children when compared with other tribes of different states was not critical.